Nutritional and Bioactive Components of Pomegranate Waste Used in Food and Cosmetic Applications: A Review - Ko, Katharine (Foods, 2021)
Pomegranate (Punica granatum L.) is a fruit that is rich in bioactive compounds that has a biowaste (rind and seed) with the potential to be converted into value-added products in a wide variety of applications. Recent studies have demonstrated the potent antioxidant and antimicrobial effects of using pomegranate rind and seed as natural food additives, thus making researchers incorporate them into bioplastics and edible coatings for food packaging. Additionally, these components have shown great plasticizing effects on packaging materials while extending the shelf life of food through active packaging. Even within skin health applications, pomegranate seed oil and its bioactive compounds have been particularly effective in combating UV-induced stresses on animal skin and in-vitro models, where cells and microorganisms are separated from the whole organism. They have also aided in healing wounds and have shown major anti-inflammatory, analgesic, and anti-bacterial properties. This review highlights all of the relevant and recent food and skin health applications found in the value-added conversion of pomegranate biowaste. The lack of research in particular areas and future outlook are also discussed.